Fast-Developing Dynamic Radiative Thermal Management: Full-Scale Fundamentals, Switching Methods, Applications, and Challenges - Xie, Long; Wang, Xuechuan; Bai, Yageng; Zou, Xiaoliang; Liu, Xinhua (Nano-Micro Letters, 2025)
Rapid population growth in recent decades has intensified both the global energy crisis and the challenges posed by climate change, including global warming. Currently, the increased frequency of extreme weather events and large fluctuations in ambient temperature disrupt thermal comfort and negatively impact health, driving a growing dependence on cooling and heating energy sources. Consequently, efficient thermal management has become a central focus of energy research. Traditional thermal management systems consume substantial energy, further contributing to greenhouse gas emissions. In contrast, emergent radiant thermal management technologies that rely on renewable energy have been proposed as sustainable alternatives. However, achieving year-round thermal management without additional energy input remains a formidable challenge. Recently, dynamic radiative thermal management technologies have emerged as the most promising solution, offering the potential for energy-efficient adaptation across seasonal variations. This review systematically presents recent advancements in dynamic radiative thermal management, covering fundamental principles, switching mechanisms, primary materials, and application areas. Additionally, the key challenges hindering the broader adoption of dynamic radiative thermal management technologies are discussed. By highlighting their transformative potential, this review provides insights into the design and industrial scalability of these innovations, with the ultimate aim of promoting renewable energy integration in thermal management applications. Highlights: 1 This review comprehensively summarizes the current state-of-the-art in dynamic radiative thermal management technology. 2 In-depth discussion of the basic principles of dynamic radiative thermal management technology, design strategies, and a list of related applications are presented. 3 An in-depth look at the challenges facing dynamic radiative thermal management technology, providing potential solutions for the future direction of the field.